Anomalous Heat Transport in Classical Many-Body Systems: Overview and Perspectives - Benenti, Giuliano; Lepri, Stefano; Livi, Roberto (Frontiers in Physics, 2020)
In this review paper we aim at illustrating recent achievements in anomalous heat diffusion, while highlighting open problems and research perspectives. We briefly recall the main features of the phenomenon for low-dimensional classical anharmonic chains and outline some recent developments on perturbed integrable systems, and on the effect of long-range forces and magnetic fields. Some selected applications to heat transfer in material science at the nanoscale are described. In the second part, we discuss of the role of anomalous conduction on coupled transport and describe how systems with anomalous (thermal) diffusion allow a much better power-efficiency trade-off for the conversion of thermal to particle current. A brief overview of research perspective in quantum systems is given.